Severity-Adjusted Dexamethasone Dosing and Tocilizumab Combination for Severe COVID-19 - Hong, Jin Yeong; Ko, Jae-Hoon; Yang, Jinyoung; Ha, Soyoung; Nham, Eliel; Huh, Kyungmin; Cho, Sun Young; Kang, Cheol-In; Chung, Doo Ryeon; Baek, Jin Yang; Sohn, You Min; Park, Hyo Jung; et al. (Yonsei medical journal, 2022)
Real-world experience with tocilizumab in combination with dexamethasone in patients with severe coronavirus disease (COVID-19) needs to be investigated. A retrospective cohort study was conducted to evaluate the effect of severity-adjusted dosing of dexamethasone in combination with tocilizumab for severe COVID-19 from August 2020 to August 2021. The primary endpoint was 30-day clinical recovery, which was defined as no oxygen requirement or referral after recovery. A total of 66 patients were evaluated, including 33 patients in the dexamethasone (Dexa) group and 33 patients in the dexamethasone plus tocilizumab (DexaToci) group. The DexaToci group showed a statistically significant benefit in 30-day clinical recovery, compared to the Dexa group ( =0.024). In multivariable analyses, peak FiO within 3 days and tocilizumab combination were consistently significant for 30-day recovery (all <0.05). The DexaToci group showed a significantly steeper decrease in FiO (-4.2±2.6) than the Dexa group (-2.7±2.6; =0.021) by hospital day 15. The duration of oxygen requirement was significantly shorter in the DexaToci group than the Dexa group (median, 10.0 days vs. 17.0 days; =0.006). Infectious complications and cellular and humoral immune responses against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in the convalescence stage were not different between the two groups. A combination of severity-adjusted dexamethasone and tocilizumab for the treatment of severe COVID-19 improved clinical recovery without increasing infectious complications or hindering the immune response against SARS-CoV-2.